The Risk of Some Veterinary Antimicrobial Agents on Public Health Associated with Antimicrobial Resistance and their Molecular Basis - Hao, Haihong; Sander, Pascal; Iqbal, Zahid; Wang, Yulian; Cheng, Guyue; Yuan, Zonghui (Frontiers in Microbiology, 2016)
The risk of antimicrobial agents used in food-producing animals on public health associated with antimicrobial resistance continues to be a current topic of discussion as related to animal and human public health. In the present review, resistance monitoring data and risk assessment result of some important antimicrobial agents were cited to elucidate the possible association of antimicrobial use in food animals and antimicrobial resistance in human. From the selected examples, it was obvious that ban on use of some antimicrobial agents (e.g. avoparcin, fluoroquinolone, tetracyclines) did not change drug resistance patterns and did not mitigate the intended goal of minimizing antimicrobial resistance. The use of some antimicrobial agents (e.g.virginiamycin, macrolides and cephalosporins) in food animals may impact on the antimicrobial resistance in humans, but it was largely depended on the pattern of drug usage in different geographical regions. The epidemiological characteristics of resistant bacteria were closely related to molecular mechanism involved in the development, fitness and transmission of antimicrobial resistance.